2020
DOI: 10.3390/microorganisms8071086
|View full text |Cite
|
Sign up to set email alerts
|

Functional Biodiversity of Yeasts Isolated from Colombian Fermented and Dry Cocoa Beans

Abstract: Yeasts play an important role in the cocoa fermentation process. Although the most relevant function is the degradation of sugars and the production of ethanol, there is little understanding of the enzyme activities and attributes that allow them to survive even after drying. The present study explored the functional biodiversity of yeasts associated with Criollo Colombian cocoa fermented beans, able to survive after drying. Twelve species belonging to 10 genera of osmo-, acid-, thermo-, and desiccation-tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 60 publications
3
31
0
2
Order By: Relevance
“…Saccharomyces cerevisiae and Wickerhamomyces anomalus were occasionally isolated from fermentation carried out in WB and PB, respectively. Our results are similar to those obtained by several authors that reported most isolated yeasts species belonging to several genus such as Pichia, Candida, Saccharomyces, Saccharomycopsis, Schizosaccharomyces, Wickerhamomyces and Cryptococcus involved in the cocoa fermentation (Mota-Gutierrez et al, 2018;Delgado-Ospina et al, 2020). The relationship between specific yeast strains and the cocoa fermentation treatment could be explained by the dynamics and interactions between yeasts and bacteria strongly depending on the method (Mota-Gutierez et al, 2018).…”
Section: Cut Test Scoresupporting
confidence: 92%
“…Saccharomyces cerevisiae and Wickerhamomyces anomalus were occasionally isolated from fermentation carried out in WB and PB, respectively. Our results are similar to those obtained by several authors that reported most isolated yeasts species belonging to several genus such as Pichia, Candida, Saccharomyces, Saccharomycopsis, Schizosaccharomyces, Wickerhamomyces and Cryptococcus involved in the cocoa fermentation (Mota-Gutierrez et al, 2018;Delgado-Ospina et al, 2020). The relationship between specific yeast strains and the cocoa fermentation treatment could be explained by the dynamics and interactions between yeasts and bacteria strongly depending on the method (Mota-Gutierez et al, 2018).…”
Section: Cut Test Scoresupporting
confidence: 92%
“…The drying treatments on the fibers are consistent with the low moisture content and water activity found, which can mean a low probability of proliferation of microorganisms that deteriorate the fibers. The pH found in the fibers is slightly acidic, in CS due to traces of organic acids originated during the fermentation and drying process of the beans [ 51 ], and in CPHF due to the ripening process. The effect of the treatments on CPH showed a significant decrease (P < 0.05) in pH ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For this, we selected the strains P. kudriavzevii ECA33 and S. cerevisiae 4, which did not show decarboxylase activity of the amino acids tested individually in this study. These strains were characterized previously by their good thermotolerance, as well as a strong pectinolytic and β-glucosidase activity in a synthetic medium [ 18 ] suggesting that they may have an important impact on cocoa production.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the maximum of lactic and acetic acid production was reached at 24 °C for SCB samples and at 48 h (lactic acid) and 72 h (acetic acid) for PKB samples. On the other hand, P. kudriavzevii ECA33 that is more thermotolerant than S. cerevisiae 4 [ 18 ], promoted a major accumulation of both lactic (19.7 ± 0.9 mg/kg) and acetic acid (71.5 ± 3.6 mg/kg), with respect to SCB and CB samples, at the end of the fermentation period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation